New Prototrochus species of sea cucumber from Australia (Echinodermata: Holothuroidea: Synaptida: Myriotrochidae) - O’loughlin, P Mark; Macintosh, Hugh (Zootaxa, 2015)
The case put by Alexey Smirnov in 2012 is accepted and the order name Synaptida Cuénot is adopted in place of Apodida Brandt. Two new Myriotrochidae Théel species from the continental slope of Australia are described: Prototrochus robbinsae sp. nov. and Prototrochus roniae sp. nov.  A key to the six Australasian species of Prototrochus Beljaev & Mironov and a distribution and depth map are provided.